2021
DOI: 10.1161/circulationaha.121.054117
|View full text |Cite
|
Sign up to set email alerts
|

One-Year Committed Exercise Training Reverses Abnormal Left Ventricular Myocardial Stiffness in Patients With Stage B Heart Failure With Preserved Ejection Fraction

Abstract: Background: Individuals with left ventricular (LV) hypertrophy and elevated cardiac biomarkers in middle age are at increased risk for the development of heart failure with preserved ejection fraction. Prolonged exercise training reverses the LV stiffening associated with healthy but sedentary aging; however, whether it can also normalize LV myocardial stiffness in patients at high risk for heart failure with preserved ejection fraction is unknown. In a prospective, randomized controlled trial, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 65 publications
0
29
0
Order By: Relevance
“…While many preventive measures are already broadly indicated (such as recommendation of regular exercise, weight loss, or control of blood pressure), others may be more optimally applied to patients at greater risk due to cost, risk, or patient burden. Examples include high intensity exercise training, pharmacologic or surgical weight loss interventions, catheter ablation for atrial fibrillation, or drug therapies, each of which could potentially reduce risk for new-onset HFpEF based upon preliminary studies, 11 , 28 30 but would ideally be applied only to high risk patients. Such strategies will require testing in future preventive trials, but the present data show that the H2FPEF score can be used to stratify risk to identify patients to enroll in such trials.…”
Section: Discussionmentioning
confidence: 99%
“…While many preventive measures are already broadly indicated (such as recommendation of regular exercise, weight loss, or control of blood pressure), others may be more optimally applied to patients at greater risk due to cost, risk, or patient burden. Examples include high intensity exercise training, pharmacologic or surgical weight loss interventions, catheter ablation for atrial fibrillation, or drug therapies, each of which could potentially reduce risk for new-onset HFpEF based upon preliminary studies, 11 , 28 30 but would ideally be applied only to high risk patients. Such strategies will require testing in future preventive trials, but the present data show that the H2FPEF score can be used to stratify risk to identify patients to enroll in such trials.…”
Section: Discussionmentioning
confidence: 99%
“…This, in combination with aging of the ventricle in older Fontan patients, will render ventricular dysfunction (systolic and diastolic) a more important issue in the years to come ( 26 ). Aging may even be accelerated in Fontan patients similarly to what has been observed in sedentary people where the left ventricle becomes stiffer (due to lack of exercise induced ventricular stretching) and evolves toward heart failure with preserved ejection fraction phenotype ( 48 , 49 ). Increased afterload (which could contribute to systolic and diastolic deterioration) has been reported, but may be secondary to decreased output in order to maintain blood pressure ( 50 ).…”
Section: Physiology Of the Fontan Circulationmentioning
confidence: 85%
“…In fact, multiple studies including randomized controlled clinical trials such as the HF-ACTION trial, systematic reviews and meta-analyses have shown that exercise is safe and improves symptoms in HF patients, both HFrEF and HFpEF patients. 5,6,[129][130][131][132][133][134][135][136][137][138][139][140][141][142][143][144] Exercise training is therefore recommended in HF patients. 5,16 Unfortunately, exercise is initially accompanied by increases in discomfort and many HF patients are apprehensive or physically challenged by non-cardiac comorbidities.…”
Section: Benefits Of Endurance Exercise In Heart Failure: Evidence Fr...mentioning
confidence: 99%
“…Clinical data also suggest that exercise is beneficial for HF patients. In fact, multiple studies including randomized controlled clinical trials such as the HF‐ACTION trial, systematic reviews and meta‐analyses have shown that exercise is safe and improves symptoms in HF patients, both HFrEF and HFpEF patients 5,6,129–144 . Exercise training is therefore recommended in HF patients 5,16 .…”
Section: Possibilities To Improve Exercise Intolerance In Heart Failurementioning
confidence: 99%